This preview shows pages 1–3. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.View Full Document
Unformatted text preview: For the expenditure function we just replace the compensated demands we have found into E = p x X + p Y Y . E = P X exp(U-(1- )ln((1- )P X / P Y )) + P Y exp(U- ln( P Y /(1- )P X )) E = [ ] [ ]---+-Px Py U Py Py Px U Px ) 1 /( ) exp( / ) 1 ( ) exp( 1---= 1 1 ) 1 ( ) exp( Py Px U E b) From E* we can solve directly for the utility level U ---= 1 1 ) 1 ( ) exp( Py Px I U -=--1 1 ) 1 ( Py Px I Ln U c) Solution for X: From the compensated demand: [ ]--=--= 1 / ) 1 ( ) exp( )) / ) 1 ln(( ) 1 exp(( ) exp( Py Px U X Py Px U X Plugging back the Indirect Utility function we get: X= I/Px The same process for Y yields: Y=(1- )I/Py...
View Full Document
- Spring '08